2021
DOI: 10.1007/s13239-020-00516-5
|View full text |Cite
|
Sign up to set email alerts
|

Special Issue on Professor John M. Tarbell’s Contribution to Cardiovascular Engineering

Abstract: Professor John M. Tarbell's contributions to the biomedical engineering community have been substantial through service, education, and research. These contributions have spanned approximately 45 years with his research efforts impactful in areas of mechanical heart valves, artificial hearts, cardiovascular fluid mechanics, vascular permeability, and mechanobiology. Professor Tarbell's legacy goes well beyond just his own research efforts, and this special issue of Cardiovascular Engineering and Technology cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
0
0
0
Order By: Relevance
“…Their ability to successfully accelerate and improve the quality of skin wound healing has been widely demonstrated in animal studies and clinical trials (Wu et al, 2007;Clover et al, 2014;Formigli et al, 2015;Zomer et al, 2020;Kerstan et al, 2022). MSCs secrete multiple cytokines and growth factors with antiinflammatory, angiogenic, proliferative, migratory and antiapoptotic effects which have been linked to their broad therapeutic application (Jo et al, 2021). It has been shown that MSCs increase tensile strength through a macrophage-dependent mechanism in wound healing in old mice, restoring the strength levels seen in younger adult mice (Lee et al, 2013).…”
Section: Regenerative Medicine Approachesmentioning
confidence: 99%
“…Their ability to successfully accelerate and improve the quality of skin wound healing has been widely demonstrated in animal studies and clinical trials (Wu et al, 2007;Clover et al, 2014;Formigli et al, 2015;Zomer et al, 2020;Kerstan et al, 2022). MSCs secrete multiple cytokines and growth factors with antiinflammatory, angiogenic, proliferative, migratory and antiapoptotic effects which have been linked to their broad therapeutic application (Jo et al, 2021). It has been shown that MSCs increase tensile strength through a macrophage-dependent mechanism in wound healing in old mice, restoring the strength levels seen in younger adult mice (Lee et al, 2013).…”
Section: Regenerative Medicine Approachesmentioning
confidence: 99%